Solving Fuzzy Nonlinear Equations Via Stirling’s-Like Method - Umar Omesa, Audu; Mamat, Mustafa; Mohammed Sulaiman, Ibrahim; Yusuf Waziri, Muhammad; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
This paper presents a Stirling-like method (SM) for solving fuzzy nonlinear equation, where the SM steps are computed at every iteration. In this method, we combine successive substitution’s and Newton’s method. Numerical experiments with encouraging results are presented that shows the efficiency of the proposed method.